Impacts of Artificial Intelligence on Student Learning: A Systematic Literature Review - Nita Ambarita; Muh. Fiqri Nurrahmatullah (Universitas Muhammadiyah Surakarta, 2024)
This research presents a systematic literature review on the impact of artificial intelligence (AI) on student learning outcomes. While previous studies have explored various aspects of AI in education, there has been a lack of comprehensive analysis specifically examining its effect on learning outcomes. The objective of this study is to provide a detailed review of the literature on the effects of AI on student learning outcomes from 2013 to 2023, employing the PRISMA methodology. From an initial pool of 1068 papers identified in the Scopus database using defined search criteria, 39 articles were selected for the final analysis. Descriptive data reveal that most of the research focuses on higher education students and aims to enhance cognitive learning outcomes. Despite being grounded primarily in empirical research, the findings suggest that AI has significant potential to enhance educational processes in both schools and universities. This study aims to elucidate how AI can improve the learning experience, identify associated challenges and risks, and underscore the importance of integrating technology into the educational system to elevate the overall quality of learning.